Der Freischütz = The free-shooter - Fisher, Burton D. (Opera Journeys mini guide series., 2002)
A comprehensive opera-guide, featuring Principal Characters in the Opera, Brief Story Synopsis, Story Narrative with Music Highlight Examples, and Burton D. Fisher's insightful and in depth Commentary and Analysis.